Oxidative Stress and the Central Nervous System - Marcello D’Ascenzo; Claudia Colussi (Antioxidants)
Reactive oxygen and nitrogen species (ROS; RNS) are natural bioproducts of cellular metabolism, particularly produced within the mitochondria during energy production [...]